2011
DOI: 10.1111/j.1464-410x.2011.10694.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival after treatment for carcinoma invading bladder muscle: a Dutch population‐based study on the impact of hospital volume

Abstract: What ' s known on the subject? and What does the study add?The subject of mortality and survival rates after radical cystectomies in high-volume hospitals in comparison to low-volume hospitals has been extensively studied. Postoperative mortality is known to be signifi cantly lower with high-volume providers, but for survival rates there was only a trend forwards this fi nding. For this reason, we performed this Dutch population-based study on survival rates, to see if we had enough power to support this trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…22 With respect to hospital volume, an analysis of Netherlands Cancer Registry data did reveal a significant mortality detriment for an annual cystectomy volume of < 10 (HR, 1.17; 95% CI, 1.01-1.35). 23 However, these analyses did not account for clustering of data or adjuvant chemotherapy in a time-dependent manner, both of which may contribute to false-positive findings. 17,18,20 Finally, Birkmeyer et al assessed the association between hospital volume and late survival in 2514 patients who underwent cystectomy using Surveillance, Epidemiology, and End Results (SEER)-Medicare linked data but failed to demonstrate a significant association in adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…22 With respect to hospital volume, an analysis of Netherlands Cancer Registry data did reveal a significant mortality detriment for an annual cystectomy volume of < 10 (HR, 1.17; 95% CI, 1.01-1.35). 23 However, these analyses did not account for clustering of data or adjuvant chemotherapy in a time-dependent manner, both of which may contribute to false-positive findings. 17,18,20 Finally, Birkmeyer et al assessed the association between hospital volume and late survival in 2514 patients who underwent cystectomy using Surveillance, Epidemiology, and End Results (SEER)-Medicare linked data but failed to demonstrate a significant association in adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the relationship between provider volume and outcome in the literature seems to indicate that better outcomes are observed by higher volume providers. [10][11][12][13][21][22][23] Recently, health policy recommendations (publicly funded [24][25][26] or private-based 27 ) have been proposed to adopt the idea of centralization or regionalization of urologic-oncology care, based on several studies. 26,[28][29][30] On the other hand, several investigators reported methodological defects in studies supporting higher volume effect after highlighting the limitations of the measures used to assess the volume-outcome relationship.…”
Section: Zakaria Et Almentioning
confidence: 99%
“…Radical cystectomy with pelvic lymphadenectomy represents a challenge for urologists and is the gold standard treatment for non-metastatic, muscle-invasive (or high-risk non-muscle-invasive) bladder cancer (8). The complications following radical cystectomy are due, in most cases, to the intestinal resection; however, Shabsigh et al (9) documented a high incidence of thromboembolic complications (8%) and bleeding complications, with a transfusion rate of ~9%.…”
Section: Introductionmentioning
confidence: 99%